Chromosome‐level reference genome for European flat oyster (Ostrea edulis L.). (22nd August 2022) - Gundappa, Manu Kumar; Peñaloza, Carolina; Regan, Tim; Boutet, Isabelle; Tanguy, Arnaud; Houston, Ross D.; Bean, Tim P.; Macqueen, Daniel J.
Abstract: The European flat oyster ( Ostrea edulis L.) is a bivalve naturally distributed across Europe, which was an integral part of human diets for centuries, until anthropogenic activities and disease outbreaks severely reduced wild populations. Despite a growing interest in genetic applications to support population management and aquaculture, a reference genome for this species is lacking to date. Here, we report a chromosome‐level assembly and annotation for the European Flat oyster genome, generated using Oxford Nanopore, Illumina, Dovetail OmniC™ proximity ligation and RNA sequencing. A contig assembly (N50: 2.38 Mb) was scaffolded into the expected karyotype of 10 pseudochromosomes. The final assembly is 935.13 Mb, with a scaffold‐N50 of 95.56 Mb, with a predicted repeat landscape dominated by unclassified elements specific to O. edulis . The assembly was verified for accuracy and completeness using multiple approaches, including a novel linkage map built with ddRAD‐Seq technology, comprising 4016 SNPs from four full‐sib families (eight parents and 163 F1 offspring). Annotation of the genome integrating multitissue transcriptome data, comparative protein evidence and ab‐initio gene prediction identified 35, 699 protein‐coding genes. Chromosome‐level synteny was demonstrated against multiple high‐quality bivalve genome assemblies, including an O. edulis genome generated independently for a French O. edulis individual. Comparative genomics was used to characterize gene family expansions during Ostrea evolution that potentially facilitated adaptation. This new reference genome for European flat oyster will enable high‐resolution genomics in support of conservation and aquaculture initiatives, and improves our understanding of bivalve genome evolution.